Structured Light: Ideas and Concepts - Angelsky, Oleg V.; Bekshaev, Aleksandr Y.; Hanson, Steen G.; Zenkova, Claudia Yu; Mokhun, Igor I.; Zheng, Jun (Frontiers in Physics, 2020)
The paper briefly presents some essential concepts and features of light fields with strong spatial inhomogeneoty of amplitude, phase, polarization and other parameters. It contains a characterization of optical vortices, speckle fields, polarization singularities. A special attention is paid to the field dynamical characteristics (energy, momentum, angular momentum and their derivatives) which are considered not only as mechanical attributes of the field but as its meaningful and application-oriented descriptive parameters. Peculiar features of the light dynamical characteristics in inhomogeneous and dispersive media are discussed. The dynamical properties of paraxial beams and evanescent waves (including surface plasmon-polaritons) are analyzed in more detail; in particular, a general treatment of the extraordinary spin and momentum, orthogonal to the main propagation direction, is outlined. Applications of structured light fields for optical manipulation, metrology, probing and data processing are described.